2019
DOI: 10.1080/10401334.2019.1613237
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Emotions and Burnout to Medical Students’ Academic Performance

Abstract: Phenomenon: Medical school curricula challenge even the most adept learner, potentially leading to feelings of burnout. When faced with uncertainties in a new curriculum, confidence in achieving academic goals may be threatened. We previously found associations between academic performance and pride, hope, anxiety, and shame in medical students. Are these emotions still associated in the context of an evolving curriculum? Approach: All 1st-and 2nd-year medical students were invited to participate in a survey s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 41 publications
5
33
1
2
Order By: Relevance
“…These results are consistent with prior evidence that has established associations between positive emotionality and self-regulation, and between negative emotionality and a lack of selfregulation [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Results presented in this research study also reveal the specific strategic coping behaviors that are associated with students' emotions and their ultimate emotional state of engagement vs. burnout, suggesting that coping strategies are a meta-emotional variable, or, as their name implies, a behavioral strategy, adjusted or maladjusted, for managing emotions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with prior evidence that has established associations between positive emotionality and self-regulation, and between negative emotionality and a lack of selfregulation [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Results presented in this research study also reveal the specific strategic coping behaviors that are associated with students' emotions and their ultimate emotional state of engagement vs. burnout, suggesting that coping strategies are a meta-emotional variable, or, as their name implies, a behavioral strategy, adjusted or maladjusted, for managing emotions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has reported factors that predict and predispose both constructs [52]. Achievement emotions (positive vs. negative) have been differentially associated with burnout [53], and engagement has been shown to favor metacognitive self-regulation and knowledge construction [54]. More recently, the duality has been conceptualized as positive learning or engagement vs. negative learning or burnout [55].…”
Section: Engagement-burnout As a Motivational Variable Of The Learninmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported factors that predict and probabilize both (Uludag and Yaratan, 2010). Thus, it has been found that academic emotions (positive vs. negative) are differentially associated with burnout (Burr and Dallaghan, 2019). It has also been found that engagement probabilizes metacognitive self-regulation and knowledge construction (Khosa and Volet, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In contrast, positive wellbeing is associated with improved mental health outcomes, academic self-efficacy, and better academic performance. [7][8][9][10][11] Studies investigating student pharmacist wellbeing have largely explored the impact of grit, resilience, selfesteem, self-awareness, and mindfulness. [12][13][14][15][16] Although individual factors likely play a role in student pharmacist wellbeing, systems factors may be the primary drivers of wellbeing, as has been suggested for the pharmacy workplace and in other fields.…”
Section: Introductionmentioning
confidence: 99%